Challenges and opportunities for breast cancer early detection among rural dwelling women in Segamat District, Malaysia: A qualitative study. - Désirée Schliemann; Wilfred Mok Kok Hoe; Devi Mohan; Pascale Allotey; Daniel D Reidpath; Min Min Tan; Nur Aishah Mohd Taib; Michael Donnelly; Tin Tin Su (PLoS ONE, 2022)
Introduction Breast cancer patients in low- and middle-income countries often present at an advanced stage. This qualitative study elicited views regarding the challenges and opportunities for breast cancer screening and early detection among women in a low-income semi-rural community in Segamat district, Malaysia. Methods Individual semi-structured interviews with 22 people (health professionals, cancer survivors, community volunteers and member from a non-governmental organization) and four focus group discussions (n = 22 participants) with women from a local community were conducted. All participants were purposively sampled and female residents registered with the South East Asia Community Observatory aged ≥40 years were eligible to participate in the focus group discussions. Data were transcribed verbatim and analyzed using thematic analysis. Results The thematic analysis illuminated barriers, challenges and opportunities across six domains: (i) personal experiences and barriers to help-seeking as well as financial and travel access barriers; (ii) primary care challenges (related to delivering clinical breast examination and teaching breast-self-examination); (iii) secondary care challenges (related to mammogram services); (iv) disconnection between secondary and primary care breast cancer screening pathways; and (v) opportunities to improve breast cancer early detection relating to community civil service society activities (i.e. awareness raising, support groups, addressing stigma/embarrassment and encouraging husbands to support women) and vi) links between public healthcare personnel and community (i.e. improving breast self-examination education, clinical breast examination provision and subsidised mammograms). Conclusion The results point to a variety of reasons for low uptake and, therefore, to the complex nature of improving breast cancer screening and early detection. There is a need to adopt a systems approach to address this complexity and to take account of the socio-cultural context of communities in order, in turn, to strengthen cancer control policy and practices in Malaysia.